The Overall Pulse Model for Water Demand of Aggregated Residential Users. (2017) - Di Palma, F.; Gargano, R.; Granata, F.; Greco, R.
Abstract: The models for the end-user demand give a detailed description of the water request, which takes into account the consumes of each dwelling. Therefore, these approaches can model the water demand at WDS nodes by aggregating the single request of each user. The effectiveness of a novel approach the Overall Pulse model (OP)- to describe the aggregated water demand has been tested. In fact, the OP model, unlike the commonly used rectangular pulse models (e.g. PRP, NSRP), does not aim to reconstruct single demand pulses as they occur when home faucets and hydro-sanitary appliances are operated, but allows the generation of the water demand as it is observed at the house water meter. This feature makes the model very versatile, allowing the direct modeling of either a single user or of a group of n users. The possibility of 'pre-aggregation' of the water demand makes it easier to take into account the spatial variability of the model parameters. In the paper, the performance of the OP model is investigated, and to this aim the generated time series are compared with the observed ones of real users. In addition, the comparison of series obtained by means of the classical PRP approach and of the OP model show the effectiveness of the latter.